2014
DOI: 10.1007/s11192-014-1437-x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors influencing scholarly performance: a multivariate study of biomedical research groups

Abstract: Bibliometric studies often measure and compare scholarly performance, but they rarely investigate why universities, departments, and research groups do have different performance. In this paper we try to explain differences in scholarly performance of research groups in terms of organizational variables. In order to do this, we extensively review the relevant literature, and develop a model using two theoretical approaches. A multivariate analysis shows which of the independent variables do play a role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 125 publications
1
29
0
2
Order By: Relevance
“…The results show that personal factors, behaviour factors and university factors are associated with the enhancement of Sustainability 2019, 11, 4804 7 of 28 research productivity in universities. According to Verbree et al [22], it is essential to examine the impact of personal factors, behavioural factors and organisational factors on academic staff in universities to improve the research productivity performance of academic staff. This research indicates that personal characteristics, behaviour and university factors have a significant relationship with research productivity for academic staff in universities.…”
Section: Personal and Organisational Factorsmentioning
confidence: 99%
“…The results show that personal factors, behaviour factors and university factors are associated with the enhancement of Sustainability 2019, 11, 4804 7 of 28 research productivity in universities. According to Verbree et al [22], it is essential to examine the impact of personal factors, behavioural factors and organisational factors on academic staff in universities to improve the research productivity performance of academic staff. This research indicates that personal characteristics, behaviour and university factors have a significant relationship with research productivity for academic staff in universities.…”
Section: Personal and Organisational Factorsmentioning
confidence: 99%
“…Communication and collaboration between team members, the role of the leader, research experience, and group size were identified as important factors to explain variation in group productivity. These factors have been examined in a large number of follow-up studies: Size and productivity (Cohen 1991; Seglen and Aksnes 2000; Guimerà et al 2005; Heinze et al 2009; Wheelan 2009; Kenna and Berche 2011; Maaike et al 2015), cooperation within groups (Andrade et al 2009), the role of the leader (Nagpaul and Gupta 1989; Hemlin 2006; Pudovkin et al 2012; Maaike et al 2015), and the groups’ importance for PhD-students (Meschitti and Carassa 2014). A review of the literature on research groups indicates that belonging to an established research group leads to higher scientific production (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is well known that institutional configurations have a deep impact on a unit's activities (Crow and Bozeman 1998), but this phenomenon has been less studied in the case of university units (see Verbree et al 2015). To our knowledge, the connection with the configuration of funding streams, and particularly with dual university funding, has rarely been made.…”
Section: Discussionmentioning
confidence: 99%